The determinants and mechanisms of residents’ green consumer behavior in Dongguan city under the carbon peak target - Yao Jia; Chonlavit Sutunyarak (Environment and Social Psychology, 2025)
Under the carbon peaking target, residents’ green consumption behavior plays a crucial role in reducing carbon emissions. This study takes Dongguan as a case to investigate the influencing factors and mechanisms of residents’ green consumption behavior, aiming to provide evidence for formulating targeted emission reduction strategies in high-carbon regions. Based on the Theory of Planned Behavior (TPB) and the Attitude-Behavior-Context (ABC) theory, the research adopts a quantitative approach, conducting a questionnaire survey among 500 residents through multi-stage stratified sampling and analyzing the data using structural equation modeling (SEM). The results indicate that green consumption awareness, perceived behavioral control, and external factors (economic, policy, and market) all have significant positive effects on green consumption behavior, while subjective norms show no significant impact. Green consumption attitudes mediate the relationship between most variables and behavior. It is recommended that the government establish a "cognition-attitude-behavior" full-chain guidance mechanism, optimize policy tools and market supply, while enterprises should develop differentiated green products for diverse consumer groups to collaboratively advance regional carbon peaking goals.